The Laic State and the Secularization of Protestant Reform: aspects on the theological foundations of modern state freedom culture - Krüger, Sabrina Alves de Jesus da Silva; Westphal, Euler Renato (Vox Scripturae - Revista Teológica Internacional, 2017)
This research shows the relationship between the Laic State and the Church. The laic state is defined and conceptualized as a state based on Christian tradition, as Scripture shapes it, through its legal laws and regulations of society. This State perspective based on the Protestant tradition is visible from Luther that exposes the two kingdoms. The temporal realm that limits non-Christians in good coexistence and protects Christians, and the nontemporal that refers to the truly Christians who live and fulfill as laws of the State in a costless way from the acting of the Spirit of God.
Keywords: Laic State; Protestant Reformation; Cultural Heritage; Secularization